LEVELS ANTIINFAMMATORY CYTOKINES (ІL-4, ІL-10) IN MAINTENCE HEMODIALYSIS PATIENTS DEPENDING ON EXPRESSED ANAEMIA AND CHARACTER DEFEAT OF KIDNEY - DudarІ.; Savchuk, V.; Gonchar, I.; Driyanska, V.; Krasjuk, E.; Khil, M. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Aims: The purpose of the present study was to compare the levels of anti-inflammatory cytokines in patients with chronic kidney disease, prolonged sessions of hemodialysis, depending on the severity of anemia. Materials and methods: We investigated 155 patients with chronic kidney disease, prolonged sessions of hemodialysis and anemia (mean age 46.4±12.4). Patients were divided into 4 groups depending on expressed of anemia: in the I-st (n=22) group – patients with the level of hemoglobin over 110g/l, in the II (n=66) group hemoglobin 90 - 110g/l, in the III (n=44) group hemoglobin 70-89 g/l, in the IV (n=22) group hemoglobin <70 g/l. Results: We have defined that level of IL-4 was clinically significantly lower (p <0.001) in patients, who have getting hemodialysis by comparison to control group. Levels of IL-4 had a significant differences between all of group of patients and controls (p <0.05). IL-10 had a positive correlation with the level of Hb (r=0.2405; p=0.003). ІL-4 had a negative correlation with the level of Hb (r=-0.4842; p <0.001). The average level of IL-4 was significantly increased in diabetic patients compared with non-diabetic patients 92±17.7 vs 48.3±28.1 (p <0.05). Conclusions: All of studied patients have had an increased level of anti- inflammatory cytokines. Serum IL-4 was higher in patients with diabetes. The levels of anti-inflammatory cytokines (IL-4 and IL-10) have had a significant correlation with the severity of anemia.